Computational screening, synthesis and neuroprotective evaluation of small molecule for the treatment of alzheimer's disease - Nerlis Pajaro-Castro; Elkin Torres-Sierra,; Edwar Cortes-Gonzalez; Margaret Paternina; Erwin Camacho; Pedro Blanco (Vitae)
BACKGROUND: Current treatments for Alzheimer’s disease primarily address symptoms, as no definitive therapeutic targets have been identified. OBJECTIVES: This study aims to conduct a virtual screening of small molecules and synthesize and evaluate one of the most promising candidates for Alzheimer’s therapy. METHODS: Using AutoDock Vina, compounds with drug-like properties were docked against key proteins implicated in Alzheimer's pathology: β-Secretase, γ-Secretase, Pin1, and Cdk5. The molecule with the highest in silico affinity (PubChem ID: 84378305) was synthesized and evaluated experimentally. Cytotoxicity and neuroprotective effects were assessed using the MTT assay in the presence of the Aβ25-35 peptide. RESULTS: Four candidate molecules showed strong binding affinity, ranging from -6.8 to -9.1 kcal/mol. The results showed that when SK-N-SH cells were simultaneously treated with Aß25-35 peptide (5 µM) and compound 84378305 (0,1 µM), the molecule exhibited significant neuroprotection (33%) after the 48 h of incubation. CONCLUSION: Findings indicate that this lead compound exhibits potential neuroprotective activity, highlighting its promise as a candidate for further development in Alzheimer’s disease treatment.